Langerhans Cell Histiocytosis Presenting as Progressively Worsening Neck Pain: A Case Report With a Review of Literature. (November 2019) - Krishnan, Nithya; Zuberi, Lara; Shukri, Amal; Gopinath, Arun; Haymes, Dalys
A 29-year-old female with past medical history of chronic serous otitis media presented with worsening neck stiffness and pain over a period of 2 weeks. The patient described non-specific symptoms that were localized to the right side of her neck. She presented to the hospital only when the pain was so extreme that it limited her range of motion. The differential for acute neck pain without fever, chills or any inciting trauma is vast. They include medical emergencies such as meningitis, acute coronary syndromes and extend to rheumatologic diseases or simply musculoskeletal strain. On review of systems, she denied dizziness, headache, vision changes, dysphagia, or other facial pain. Based on the severity of her pain, she underwent a Computed Tomography scan of the neck, which was concerning for erosive calavarial lesions. Further imaging revealed multiple lytic foci and erosions from the right maxillary sinus to the right mandible to the C1 vertebra. Following requisite surgical intervention, she was found to have Langerhans cell histiocytosis, a rare disease of myeloid cells, usually affecting pediatric populations. Little is known about the adult manifestations of Langerhans Cell Histiocytosis. This review contributes to broadening the literature on this topic which can present with complaints as typical as neck pain.